Posture analysis of the workers of railway maintenance unit - Maharani, Ade Tria; Hariyono, Widodo (Periodicals of Occupational Safety and Health, 2023)
Maintenance of railways is done periodically by the railway maintenance unit. The work activities executed in uncertain weather and with the use of relatively heavy equipments are done in a quick manner. Therefore, work posture examination is required using Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM) methods. This study aimed to find out the work posture of the workers in the railway maintenance unit of Resort IV.6 Ketapang, North Lampung. The study was qualitative in nature using a case study approach. The data were collected through interviews and observation using Nordic Body Map (NBM) forms. Data collection from informants was conducted using purposive sampling with 1 key informant and 4 triangular informants, with the characteristics of already working for more than 3 years and also being the workers in the railway raising projects. The results of the study showed that, based on REBA calculation, the score obtained upon the observation of the informants’ working posture was 10, which was categorized as high. As such, immediate identification is required regarding the informants’ working posture. Based on the results of the study, it is concluded that working postures of the workers in the railway maintenance unit have effects on the pain in the muscle parts of the workers. Therefore, Improvement on working postures should be made immediately. In addition, during their work using working equipments, they should do short stretching to reduce the pain complained.